Study on Soil Conservation in the Catchment Areas Above Dams in River Valley Projects Part I - Planning Commission (Planning Commission, 1966)
During the Third Five-Year Plan soil conservation work on thirteen river valley projects involving about three thousand square kilometres area was taken up. The problem is enormous and, at the same time, complex, as every water-shed has its own characteristics and problems requiring its own programme of soil conservation measures. No general rule or programme suggested for a particular river valley project can be applied universally. The programme of soil conservation in some cases requires bonding or terracing for preventing or control of surface run-off, reclamation for agricultural and forestry uses etc., while in others, data are to be first collected in respect of soil types, slopes, degrees of erosion, stream flow, sedimentation etc., before suggesting methods for more fruitful utilisation of the river basins.
Committee on Natural Resources Government of India Planning Commission
Committee on Natural Resources Government of India Planning Commission